How to Spot a Careerist Early On: Psychopathy and Exchange Ideology as Predictors of Careerism - Chiaburu, Dan S.; Muñoz, Gonzalo J.; Gardner, Richard G. (2013)
Careerism refers to an individual’s propensity to achieve their personal and career goals through nonperformance-based activities (Feldman, The Indus Org Psychol 39–44, 1985). We investigated the role of several dispositional predictors of careerism, including Five-factor model (FFM) personality traits, primary psychopathy, and exchange ideology. Based on data from 131 respondents, as expected, we observed that emotional stability was negatively correlated with careerism. Primary psychopathy and exchange ideology explained additional variance in careerism after accounting for FFM traits. Relative importance analyses indicated that psychopathy (relative weight percentage of explained variance = 42.1 %) and exchange ideology (relative weight percentage = 44.1 %) were equally important in predicting careerism. We highlight the need for future research efforts investigating the combined effects of contextual factors—particularly, human resource practices—and individual differences to understand careerism in the workplace.
Keywords: Relative importance analysis; Dark side personality; Exchange ideology; Psychopathy; Five-factor model; Careerist orientation; Careerism